2020
DOI: 10.7554/elife.57390
|View full text |Cite
|
Sign up to set email alerts
|

Population-scale proteome variation in human induced pluripotent stem cells

Abstract: Human disease phenotypes are ultimately driven primarily by alterations in protein expression and/or function. To date, relatively little is known about the variability of the human proteome in populations and how this relates to variability in mRNA expression and to disease loci. Here, we present the first comprehensive proteomic analysis of human induced pluripotent stem cells (iPSC), a key cell type for disease modelling, analysing 202 iPSC lines derived from 151 donors, with integrated transcriptome and ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 69 publications
(128 reference statements)
3
38
0
Order By: Relevance
“…Across several species, half or more of cis -eQTLs were reported to also affect protein abundance, suggesting high levels of agreement between mRNA and protein ( Albert et al, 2018 ; Albert et al, 2014b ; Hause et al, 2014 ; Skelly et al, 2013 ). However, other work found many cis -eQTLs whose effects on protein were smaller than those on mRNA, suggesting the existence of mechanisms that buffer protein levels against variation in mRNA abundance ( Battle et al, 2015 ; Ghazalpour et al, 2011 ; Mirauta et al, 2020 ). Trans -acting QTLs were reported to show even greater differences between mRNA and protein.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Across several species, half or more of cis -eQTLs were reported to also affect protein abundance, suggesting high levels of agreement between mRNA and protein ( Albert et al, 2018 ; Albert et al, 2014b ; Hause et al, 2014 ; Skelly et al, 2013 ). However, other work found many cis -eQTLs whose effects on protein were smaller than those on mRNA, suggesting the existence of mechanisms that buffer protein levels against variation in mRNA abundance ( Battle et al, 2015 ; Ghazalpour et al, 2011 ; Mirauta et al, 2020 ). Trans -acting QTLs were reported to show even greater differences between mRNA and protein.…”
Section: Introductionmentioning
confidence: 93%
“…It is also unclear to what extent there are protein-specific pQTLs that influence protein abundance without affecting the mRNA of the same gene. Recent studies have begun to address these questions ( Battle et al, 2015 ; Cenik et al, 2015 ; Chick et al, 2016 ; Foss et al, 2011 ; Foss et al, 2007 ; Ghazalpour et al, 2011 ; Großbach et al, 2019 ; Mirauta et al, 2020 ; Picotti et al, 2013 ; Sun et al, 2018 ; Wu et al, 2013 ; Yao et al, 2018 ) and reported a wide range of observations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, we estimated a large proportion of shared genetic regulation across gene expression and proteins. However, as reported by others before 5,1618,22,23 , the genetic regulation of circulating proteins seems to involve additional protein specific regulatory processes that complicates the identification of genomic regions acting in both phenotypes.…”
Section: Introductionmentioning
confidence: 87%